2023
DOI: 10.1371/journal.pgph.0001667
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Hepatitis C virus self-testing in four settings

Abstract: Globally, there are approximately 58 million people with chronic hepatitis C virus infection (HCV) but only 20% have been diagnosed. HCV self-testing (HCVST) could reach those who have never been tested and increase uptake of HCV testing services. We compared cost per HCV viraemic diagnosis or cure for HCVST versus facility-based HCV testing services. We used a decision analysis model with a one-year time horizon to examine the key drivers of economic cost per diagnosis or cure following the introduction of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The cost of testing has been identified as an important barrier to HCV testing [ 13 ]. Whilst our study did not evaluate a long enough time horizon to capture the benefits of treatment, we provide evidence to support the findings of a modelling study by the WHO which explored the cost-effectiveness of HCV self-testing in China, Georgia, Vietnam and Kenya [ 42 ]. The cost-effectiveness of HCV self-testing is driven by its potential to increase the number of people tested so that they may be successfully treated to eliminate onward transmission; this ultimately reduces the HCV burden in a community.…”
Section: Discussionmentioning
confidence: 52%
“…The cost of testing has been identified as an important barrier to HCV testing [ 13 ]. Whilst our study did not evaluate a long enough time horizon to capture the benefits of treatment, we provide evidence to support the findings of a modelling study by the WHO which explored the cost-effectiveness of HCV self-testing in China, Georgia, Vietnam and Kenya [ 42 ]. The cost-effectiveness of HCV self-testing is driven by its potential to increase the number of people tested so that they may be successfully treated to eliminate onward transmission; this ultimately reduces the HCV burden in a community.…”
Section: Discussionmentioning
confidence: 52%
“…An additional advantage of these testing strategies is that POC anti-HCV and HCV RNA testing using fingerstick blood samples is generally well regarded by patients in terms of ease, acceptability, and preference compared with venipuncture [170,171]. A large evaluation of the cost-effectiveness of HCV self-testing in four different countries demonstrated that self-testing was not cost-efficient, but that it significantly increased the number of diagnosed and cured individuals [172]. However, cost differences were driven primarily by the treatment price and not the cost of diagnosis.…”
Section: Hepatits C Virusmentioning
confidence: 99%